THROMBOSIS DAN USIA LANJUT - Bakta, I Made (journal of internal medicine; Vol. 8, No. 2 Mei 2007)
Thrombosis, venous as well as arterial thrombosis, is the basic pathogenetic mechanism which leads to high morbidity and mortality diseases. The Virchow triad is the basic mehanism of pathogenesis of thrombosis, ie abnormality of vessel wall, disturbances of blood flow, and abnormality of blood coagulation (hypercoagubility state). The risk factors for thrombosis could be classified into 3 main categories: situational risk factors, hereditary thrombophilia, and acquired thrombophilia. The incidence of thrombosis is higher in old people, old age is categorised as one of the risk factors of thrombosis. The mechanism of old age in promoting thrombosis is not well understood. It is assumed that in old age there is imbalance between protrombotic and antithrombotic factors, the increase of protrombotic factors are higher than antithrombotic factors.The increase of coagulation factors (fibrinogen, prothrombin, factor VII, factor VIII, von Willebrand factor, and plasminogen activator inhibitor) were increased in old age population. Recently, the genetic mechanism of age regulation synthesis of factor IX and protein C was found. Atherothrombosis is a new concept, in which thrombus deposition occured on an atheromataous plaque. Atherothrombosis gives principal clinical manifestations as coronary artery disease, acute myaocardial infarction and unstable angina, ischaemic stroke, and peripheral arterial disease. Venous thrombosis, especially on deep vein, gives clinical manifestation as deep vein thrombosis (DVT), which is frequently followed by pulmonary emboli (PE). The combination of DVT and PE is known as venous thromboembolism (VTE). The concept of thrombosis management should be based on its pathogenesis. In arterial thrombosis, the main therapy is administration of antiplatelet drug and anticoagulant to prevent the deposition of thrombus, while thrombolytic or fibrinolytic drugs are given to dissolve the preformed thrombi. In venous thrombosis antiplatelet drug is not effective. Basically, the treatment of thrombosis in old age is not different from the treatment of thrombosis in general. But in old people the comorbids are more frequent, drug interaction should be taken into special consideration.
Keywords: thrombosis, old age, atherotrombosis